The Emergence Of Muslim Ideology In The Reporting Of Palestinian And Israeli Conflict: A Study On Al-Jazeera News - Muhd Zaki Mustafa; Mohd Faizal Kasmani; Suria Hani A. Rahman; Sofia Hayati Yusoff; Noor Adzrah Ramle (Universiti Sains Islam Malaysia, 2024)
Al-Jazeera has given its estimated 35 to 45 million viewers within the Muslim world, daily news feed that stands up to its network slogan "The Opinion and the Other Opinion". The network has been the important source and for the first time, represents not only the voice of Arab region, but also the voice of Islamic world into the international news agenda. Therefore, it is vital to understand the discourse presented in the news to understand its meaning and direction. This study analyzes the news clips of Al-Jazeera English coverage of the war in Gaza which started on December 27, 2008 and ended on January 21, 2009. Analysis of the clips has been done using Critical Discourse Analysis (CDA), which assumes language and social process are deeply implicated with one another Findings identified (5) distinctive discourses from the selected news clips. Among themes are "Israels are attacking Palestinian, not only Hamas", and "The Zionists keeps lying"; which interlinked as it highlighted a continuous suppression towards Palestinian by Israeli. For Al-Jazeera, this can be regarded as counter discourse to the western media reporting on the conflict.